2021
DOI: 10.14302/issn.2379-7835.ijn-21-3908
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in Africa: Causes, Dietary Intervention, and Lifestyle Change

Abstract: Colorectal cancer (CRC) is a menace in the global public health system. According to GLOBOCAN reports, colorectal cancer is the second most diagnosed cancer in the world with more than 1.9 million cases and 935,000 deaths in 2020 alone. Diet plays a key role in exposing humans to environmental carcinogens and anti-carcinogens, consequently mitigating or aiding in the development of various cancers. CRC is most prevalent in western countries with a high intake of saturated fats, refined carbohydrates, and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 81 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…These staple foods have substances with anticarcinogenic properties such as polyphenols, minerals and vitamins. A high content of non-digestible carbohydrates (NDCs) such as fibre and resistant starch are found in roots and tubers [ 41 ]. Our study showed that consumption of potatoes at a frequency of two to three times/weekly was associated with a reduced likelihood of CRC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These staple foods have substances with anticarcinogenic properties such as polyphenols, minerals and vitamins. A high content of non-digestible carbohydrates (NDCs) such as fibre and resistant starch are found in roots and tubers [ 41 ]. Our study showed that consumption of potatoes at a frequency of two to three times/weekly was associated with a reduced likelihood of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that compared to potato starch, resistant starch from maize, produces more butyrate, which is preferable for colonocytes [ 42 ]. Our findings showed that the consumption of potatoes 2-3x/weekly, was protective against CRC, as it is a high-fibre food which produces short-chain fatty acids, particularly butyrate which is preferable for colonocytes and this high-fibre food also produces antioxidants [ 41 ]. The Ugandan diet tends to consist of a variety of potatoes, millet-based meals, maize and cassava, and hence, these high-fibre foods tend to be protective against CRC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations